Analisa Kerusakan Perkerasan Jalan Aspal - Amri Amri; Winayati Winayati; Lusi Dwi Putri (Center for Research and Community Service (LPPM) University of Abulyatama, 2021)
The road Kari Taluk Kuantan Terminal is a cross-road with flexible pavement that has suffered severe damage. The research objective was to find the remaining life of the pavement plan and the degree of damage to the asphalt pavement, using the Bina Marga method. During the service period, the pavement will experience repeated loading which causes damage, especially on the road section of the Terminal Kari Teluk Kuantan, Kuantan Singingi Regency STA 2 + 700 to 4 + 175. The results of the analysis that have been done, that: The remaining life of the pavement for the next 10 years = 12%, with a Truck Factor 0.465 <1, which means that the road is not fit to pass, The degree of damage for light front wheel vehicles is 0.0001, bus 0.0246, Truck 2 as 0.0178. The degree of damage for light vehicle rear wheels is 0.0001, buses 0.1245, Truck 2 as 0.0900, meaning that the average degree of damage for light vehicles and heavy vehicles, is less than one axis, in this case the damage is classified as collapse due to damage, with vehicle load normal which does not really affect the degree of damage to the road.